2022
DOI: 10.1088/1742-6596/2385/1/012139
|View full text |Cite
|
Sign up to set email alerts
|

How incoming turbulence affects wake recovery of an NREL-5MW wind turbine

Abstract: The present work aims at investigating the effect of inflow turbulence on the wake recovery of the NREL-5MW reference wind turbine. The wake produced by a utility-scale wind turbine invested by both a laminar uniform inflow and a turbulent flow, is analyzed by means of proper-orthogonal decomposition (POD). The considered turbine is the NREL-5MW at tip-speed ratio λ = 7 and a diameter-based Reynolds number of the order 108. The flow is simulated through Large Eddy Simulation, where the forces exerted by the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Thus, the features of the inflow turbulence appear to drive those developed in the wake exogenously. The impact of these flow structures on wake recovery has been further investigated by Cherubini et al [18] using POD. It has been found that while POD modes related to the tip and root vortices sustain the velocity gradient [19], the low-frequency flow structures exogenously triggered by the turbulence at the inflow contribute positively to wake recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the features of the inflow turbulence appear to drive those developed in the wake exogenously. The impact of these flow structures on wake recovery has been further investigated by Cherubini et al [18] using POD. It has been found that while POD modes related to the tip and root vortices sustain the velocity gradient [19], the low-frequency flow structures exogenously triggered by the turbulence at the inflow contribute positively to wake recovery.…”
Section: Introductionmentioning
confidence: 99%